Chemical Compositions and in vitro Antioxidant Activity of the Essential Oil from Coreopsis tinctoria Nutt. Flower. Issue 4 (4th July 2018) - An, Lei; Sun, Yuchen; Huang, Jia; Liu, Yuping; Yuan, Hua; Zhang, Runjun; Sun, Yufeng
Abstract: The aim of present study was to investigate chemical compositions and in vitro antioxidant activity of essential oil (EO) from Coreopsis tinctoria Nutt flower obtained in Huocheng County of China. The EO was extracted by steam distillation, its chemical compositions was analyzed by GC-MS, and its antioxidant activity was evaluated by the radical (DPPH and ABTS) scavenging capacity and ferric reducing antioxidant power (FRAP) assays. Eighty-nine compounds in the EO were identified, and the major components were limonene, (-)-carvone, α-pinene, linalool, linalyl acetate, α-bergamotene, cis -carveol, α-curcumene, thymol methyl ether, etc. The antioxidant results showed the scavenging capacity of DPPH and ABTS were as 106.28±11.45 μmol Trolox /g EO and 48.72±5.23 μmol Trolox /g EO, respectively, and the reducing power of Fe 3+ ions was as 67.40±0.69 μmol Trolox /g EO.